Manejo da hipertensão intracraniana no trauma cranioencefálico pediátrico - Jonhatan Diego Furquim; Ana Carolina Liermann; Ana Flavia Filipczak; Daniela Carolina Tomasini; Paulo Ramos David João; Polyana Monique Santos (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To review current management of intracranial hypertension in pediatric population, its evidence levels and possible complications of its application. METHODS: Bibliographic review, based on PubMed data. It was reviewed 47 articles, from April 17th to 25th of 2021, matching to "pediatric TBI, pediatric HICP, HICP management in pediatrics", we included those, in Portuguese and English, upper to 1999, and excluded 22 that were about adult TBI and HICP, scales application in TBI, management of any other complications instead HICP and genetic related outcomes post-TBI. RESULTS: Authors noticed that some measures to manage the intracranial hypertension are consensual among some authors, even with its low evidence level, however, some remain controversial. CONCLUSION: Even though many measures still have a low evidence level, they have shown positive results preventing a second insult that may lead to a secondary injury. However, it is needed an individual assessment to decide which measures are more suitable and offer a lower complications risk to the patient.